PENGEMBANGAN MEDIA PEMBELAJARAN SEPAKTAKRAW BERBASIS ANDROID BAGI PESERTA DIDIK KELAS X SMA NEGERI 1 DEMAK (Indonesian Journal for Physical Education and Sport, 2021)
Technology is developing rapidly, the use of model and media learning must also keep up with technological developments. Matter of learning which of printed books are still used in the school, but on this current development, it is necessary to conduct learning that utilizes other media such as computers / laptops, even smartphones. This research aims to develop media learning based on android Sepaktakraw which is applied to class X students of Senior High School 1 Demak. The method used in this research is Research and Development (R&D). In this research, the steps was taken included potential analysis and problem, data collection, product design, design validation for media and material experts, design revisions, product testing, and product revisions. Does android applications using Android Studio software with 3 tests, namely functionality testing with black box, validation of designs by media experts and material experts, and student acceptance by class X Senior High School Negeri 1 Demak. The results of this research indicate that the application of Android-based Sepaktakraw learning media is in the category of feasible use in learning based on functionality testing and expert validation. From the analysis of functionality testing (the black-box test gets 100% results), the media test gets 100% results and the material tests get 100% results. The results of the analysis of student acceptance of the media learning based on android Sepaktakraw application showed very positive with an average percentage per aspect of 83,20%.